Pelatihan Pembuatan Sabun Cuci Piring Ramah Lingkungan Bagi Kaum Perempuan Di Desa Toobaun, Kecamatan Amarasi Barat, Kabupaten Kupang - Roman, Maya Fitriani; Abdonia W. Finmeta; Deglori Tunmuni (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The training on environmentally friendly liquid dish soap making aims to enhance the potential of the community, particularly women, in reducing the consumption of commercial dish soap while improving household economic welfare. Soap is an essential material used for cleaning kitchen utensils and household equipment. This article presents the results of a Community Service Program focused on producing eco-friendly dishwashing soap using texapon as the main surfactant. The activities include the introduction of tools and materials, production processes, step-by-step procedures, outcomes, and benefits. A qualitative-descriptive approach was applied in this program. The partners involved were women’s groups in Toobaun Village, Amarasi Barat Subdistrict, Kupang Regency, East Nusa Tenggara. This program is expected to promote economic independence and reduce negative environmental impacts.